Application of Advanced Technology on Transport Ships as a Technological Revolution in the Maritime Industry - Kyaw, Aung Ye (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2024)
The maritime industry is experiencing a technological revolution driven by the application of advanced technology to transport vessels. This research aims to explore the impact of advanced technologies, such as satellite navigation systems, electric propulsion, advanced sensors, and data analysis, on operational efficiency, safety, and sustainability in the shipping industry. The research methodology includes a comprehensive literature review, semi-structured interviews with industry experts, case studies on ships employing advanced technologies, and data analysis using qualitative and quantitative methods. The research results show significant improvements in fuel efficiency, reduced emissions, improved condition monitoring, and predictive maintenance on ships equipped with advanced technology. However, the research also revealed challenges in implementation and adoption, including high initial costs, lack of supporting infrastructure, the need for crew retraining, and regulatory challenges. Despite this, the future potential for the application of advanced technologies in the maritime industry remains promising, with rapid developments in artificial intelligence, autonomous technologies, and blockchain. This research highlights the need for collaboration between industry stakeholders, continued investment in research and development, and conducive regulatory support to realize the full potential of the technological revolution in the maritime industry. The findings from this research contribute to a better understanding of the transformative impact of advanced technology in shipping and highlight its role in driving the industry toward a more efficient, sustainable, and safe future.